Characterization of Layer-by-Layer Biodegradable Films Based on Hydroxypropyl Methylcellulose-Nanochitosan - Muna, Aulal; Wicaksono, Rumpoko; Wibowo, Condro (Diponegoro University, 2023)
This research investigates the physical and optical properties of single-layer and layer-by-layer biodegradable films composed of hydroxypropyl methylcellulose (HPMC) and nanochitosan. Initially, HPMC and nanochitosan were formulated as single layers at various concentrations, and subsequently, the selected formulas were utilized to produce a layer-by-layer film. The results indicate that the concentrations of 0.4% w/v HPMC and 0.5% w/v of nanochitosan were successfully assembled into a layer-by-layer biodegradable film. Assessment based on multiple parameters (thickness, moisture content, water vapor transmission rate, color, transparency, and biodegradability) reveals that the deposition of nanochitosan onto HPMC in a layer-by-layer configuration enhances most characteristics of single-layer HPMC films, with the exception of optical properties. Moreover, all samples were degraded within a seven-day observation period.